Knowledge, attitudes and practices in relation to maternal health care in rural Nepal: A study of married women of reproductive age and their household heads. - Tamang, Laxmi (2006)
ABSTRACT: Maternal health care (MHC) services are not being utilized effectively in Nepal where complications related to pregnancy, childbirth and puerperium account for one-third of all deaths among women of reproductive aged, 15 to 49 years. Nine out of ten women give birth at home, under less than sterile conditions, and without the help of a skilled health care provider. This study explores the knowledge, attitudes and practices of married women of reproductive age (MWRA) and their household heads in relation to MHC with a view to enhancing the effectiveness of public health education to boost the utilization of MHC services. Media preferences for the delivery of health messages were also explored. A household level cross-sectional survey by questionnaire was carried out at household level among 336 MWRA and 335 household heads. They came from 14 villages in a single district. Some of the villages had participated in an integrated community-based family health program and some had not. Comparisons are made between them. The main findings were that only 0.6% of MWRAs had presented for the recommended four or more antenatal visits, over 80% had their most recent births at home and only around 30% had presented for a postnatal checkup. Only around 11% of MWRAs and household heads had heard of safe motherhood. Household head, who are very influential in Nepal over decisions about maternal health care, had significant gaps in their understanding of this concept. Both household heads and MWRAs revealed a poor knowledge of the optimal timing for antenatal and postnatal visits, the recommended number of antenatal visits and the danger signs during pregnancy, labour and postpartum that indicate the need for urgent public health attention. Respondents from villages that had been exposed to the intervention had fewer negative attitudes to utilization of health services but there were frequently voiced misconceptions in respondents from both types of village that antenatal care was only necessary if particular problems arose, that eating green vegetables may cause illness in mothers and newborn and that smoke filled rooms helped protect mothers and babies from cold and evil spirits. The study concludes that qualitative investigations of this type provide the background understanding of target communities that is essential for the design of effective public health campaigns and appropriate modes of health care to reduce the barriers to utilization that currently exist in rural Nepal. Key words: Maternal health care, knowledge, attitude, practice, antenatal care, safe motherhood, childbirth, labour, postnatal care.